Large-Scale Crustal-Block-Extrusion During Late Alpine Collision - Marco Herwegh (Nature Portfolio, 2017)
Abstract The crustal-scale geometry of the European Alps has been explained by a classical subduction-scenario comprising thrust-and-fold-related compressional wedge tectonics and isostatic rebound. However, massive blocks of crystalline basement (External Crystalline Massifs) vertically disrupt the upper-crustal wedge. In the case of the Aar massif, top basement vertically rises for >12 km and peak metamorphic temperatures increase along an orogen-perpendicular direction from 250 °C–450 °C over horizontal distances of only <15 km (Innertkirchen-Grimselpass), suggesting exhumation of midcrustal rocks with increasing uplift component along steep vertical shear zones. Here we demonstrate that delamination of European lower crust during lithosphere mantle rollback migrates northward in time. Simultaneously, the Aar massif as giant upper crustal block extrudes by buoyancy forces, while substantial volumes of lower crust accumulate underneath. Buoyancy-driven deformation generates dense networks of steep reverse faults as major structures interconnected by secondary branches with normal fault component, dissecting the entire crust up to the surface. Owing to rollback fading, the component of vertical motion reduces and is replaced by a late stage of orogenic compression as manifest by north-directed thrusting. Buoyancy-driven vertical tectonics and modest late shortening, combined with surface erosion, result in typical topographic and metamorphic gradients, which might represent general indicators for final stages of continent-continent collisions.